Weak polynomial topology and weak analytic topology on Banach spaces and on Freshet spaces - A. V. Zagorodnyuk; M. A. Mytrofanov (Karpatsʹkì Matematičnì Publìkacìï, 2013)
We investigate under which conditions weak polynomial or weak analytic topology (*-weakpolynomial or *-weak analytic topology) coincides whith the norm topology on a real (complex) Banach or Freshet space.